LEARNING AND PRACTICING ARTIFICIAL INTELLIGENCE FOR MOVIE SUBTITLING CLASS - Juliansyah; -, Suranto; Trisno Adi, Bambang; -, Kusbandi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Semester Learning Plan (RPS) serves as a crucial guide for educators. However, it is often observed that an RPS may fall short ineffectively guiding educators due to its failure to keep pace with technological advancements. Consequently, educators must engage in innovative practices. This observation underscores the necessity for developing a learning model that is more aligned with technological trends. A learning model is essentially a framework that can be as a standard or reference for educational practices. One particular model that is set to be developed is the learning model for the course Movie Subtitling. This initiative arises from the recognition that the current RPS for this course includes learning activities that lack innovative technological integration and do not introduce new knowledge, as it primarily focuses on analysing translation outcomes. More critically, the existing RPS for Movie Subtitling does not provide students with opportunities to acquire knowledge or practical experience in utilizing Artificial Intelligence-based translation applications. The discussion related to Artificial Intelligence (AI) has become increasingly interesting, particularly within the realm of translation. This interest extends specifically to the subtitling of films. However, research aimed at developing learning models that optimize the use of AI-driven translation applications remains limited. In this context, the findings of this research emerge as particularly significant. Key findings include: 1) An analysis and explanation of the format and content of the pre-development RPS, 2) Insights into the rationale for the necessity of developing the RPS, 3) A detailed explanation of the process involved in developing the newly designed learning model, and 4) An exploration of AI-based translation applications that can be integrated within the developed learning framework.